2002
DOI: 10.1023/a:1014691416614
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper describes a disposable¯ow cytometer that uses an air-liquid two-phase micro¯uidic system to produce a focused high-speed liquid sample stream of particles and cells. The susceptibility of thin liquid columns to instabilities may suggest that focusing of sample liquids with streams of air would be dif®cult. The design of channel geometry, control of¯ow rates, and use of appropriate surface chemistries on the channel walls, however, enabled the generation of thin (15±100 lm) and partially bounded samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 21 publications
0
66
0
Order By: Relevance
“…Initially, liquid is injected into the plug generator and focused by air flows to form a stable stratification of air and liquid (Fig. 3A) (51,52). When air is valved off, the liquid stream spreads instantaneously and progresses gradually into the culture chamber (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, liquid is injected into the plug generator and focused by air flows to form a stable stratification of air and liquid (Fig. 3A) (51,52). When air is valved off, the liquid stream spreads instantaneously and progresses gradually into the culture chamber (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic systems in this realm offer the benefit of highly predictable behavior that does not depend on sample size desirable qualities for a microfluidic sample positioning system. Numerous structures [17][18][19][20][21][22][23][24][25] have been designed for hydrodynamic flow focusing under this approximation and will be discussed in Sec. II A.…”
Section: Review On Recent Advancement On Microfluidicsmentioning
confidence: 99%
“…In a related approach, air can be used as the sheath fluid to confine the sample flow while reducing the volume of the clean water needed. 18 Two-dimensional flow focusing constrains the sample flow in the lateral direction; however, the fluid velocity still exhibits a parabolic velocity profile in the vertical direction.…”
Section: A Hydrodynamic Focusingmentioning
confidence: 99%
“…Studies on the enumeration of C2C12 myoblast cells using air pressure [77,78] and of blood cells using a sheathfree transport system [31] are interesting. In addition to an analysis of suspended cell populations (e.g., red blood cells, platelets, lymphocytes, monocytes, and granulocytes), Ferris et al [58] also performed viral analysis, and demonstrated the rapid enumeration of adenovirus, respiratory syncytial virus, and influenza virus.…”
Section: Biomedical Informationmentioning
confidence: 99%